Crack mode and life of Ti-6Al-4V under multiaxial low cycle fatigue (Fracture and Structural Integrity, 2015)
This paper studies multiaxial low cycle fatigue crack mode and failure life of Ti-6Al-4V. Stress controlled fatigue tests were carried out using a hollow cylinder specimen under multiaxial loadings of ?=0, 0.4, 0.5 and 1 of which stress ratio R=0 at room temperature. ? is a principal stress ratio and is defined as ?=sigmaII/sigmaI, where sigmaI and sigmaII are principal stresses of which absolute values take the largest and middle ones, respectively. Here, the test at ?=0 is a uniaxial loading test and that at ?=1 an equi-biaxial loading test. A testing machine employed is a newly developed multiaxial fatigue testing machine which can apply push-pull and reversed torsion loadings with inner pressure onto the hollow cylinder specimen. Based on the obtained results, this study discusses evaluation of the biaxial low cycle fatigue life and crack mode. Failure life is reduced with increasing ? induced by cyclic ratcheting. The crack mode is affected by the surface condition of cut-machining and the failure life depends on the crack mode in the multiaxial loading largely.
Keywords: Hollow cylinder specimen